Ruptured Pancreaticoduodenal Artery Aneurysms Associated with Celiac Stenosis Caused by the Median Arcuate Ligament: A Poorly Known Etiology of Acute Abdominal Pain. Issue 2 (February 2016) - Chivot, C.; Rebibo, L.; Robert, B.; Regimbeau, J.-M.; Yzet, T.
Abstract : Objective/Background: Pancreaticoduodenal artery (PDA) aneurysm is a rare but clinically important form of vascular disease. A small proportion of these aneurysms are caused by compression of the artery by the median arcuate ligament (MAL). The objective of the study was to establish whether it is feasible and effective to treat ruptured PDA aneurysms without treating the celiac stenosis caused by the MAL. Methods: From January 2007 to November 2014, 10 patients were included. Standard embolization or surgical procedures were used to treat the ruptured aneurysms, but the celiac stenosis itself was not treated. The primary end point was the feasibility and efficacy of embolization for the treatment of ruptured PDA aneurysms. The secondary end points included clinical data, imaging findings, the success rate of embolization and the outcome during follow up. Results: All patients presented with acute, non-specific epigastric pain with nausea. An abdominal computed tomography scan revealed peri-pancreatic hematoma in all cases, and PDA aneurysms were visible in six patients. The aneurysms ranged from 2 mm to 10 mm in diameter and were variously located on the anterior PDA ( n = 1), the posterior PDA ( n = 3), and the branch of the dorsal pancreatic artery ( n = 6). Surgery was performed in two cases (with one death). Embolization was successful in the other eight cases. The median length of hospital stay was 10 days (range 8–25 days). Over a median follow up period of 11 months (range 5–48 months), none of the PDA aneurysms recurred. Conclusion: Rupture of a PDA aneurysm caused by the MAL should always be considered in the differential diagnosis of acute abdominal pain, because the condition requires specific management. Embolization is safe and has a high success rate. Surgery should only be performed when embolization fails.